Sobre la presencia de Astragalus guttatus Banks & Solander, en la provincia de Almería. On the presence of Astragalus guttatus Banks & Solander in the province of Almería - López García, David; JIménez Martínez, Juan Francisco; Sánchez Gómez, Pedro (Acta Botanica Malacitana, 2012)
On the presence of Astragalus guttatus Banks & Solander in the province of Almería. Palabras clave. Astragalus, corología, conservación, Almería, Andalucía. Key words. Astragalus, chorology, conservation, Almeria, Andalusia.